mRNA profilin identifies low levels of phosphatases dual‐specific phosphatase‐7 (DUSP7) and cell division cycle‐25B (CDC25B) in patients with early arthritis - Castro‐Sánchez, P.; Ramirez‐Munoz, R.; Lamana, A.; Ortiz, A.; González‐Álvaro, I.; Roda‐Navarro, P. (Clinical and experimental immunology, 2017)
Summary Phosphotyrosine phosphatases (PTPs) control phosphorylation levels and, consequently, regulate the output of intracellular signalling networks in health and disease. Despite the high number of PTPs expressed in CD4 T cells and their involvement in autoimmunity, information about the expression profile of PTPs in these cells has not been obtained in patients diagnosed with autoimmune diseases. Here, we compare the expression profile of PTPs in CD4 T cells of healthy volunteers and patients submitted to an early arthritis clinic, due to suspicion of rheumatoid arthritis, an autoimmune disease mediated by CD4 T cells. We found lower transcript levels of the mitogen‐activated protein kinase (MAPK) phosphatase dual‐specific phosphatase‐7 (DUSP7) and the cell division cycle‐25B (CDC25B) in T cells of patients. While the low expression level of DUSP7 was restricted to patients with positive rheumatoid factor and anti‐citrullinated protein antibodies, the altered expression of CDC25B correlated with the activity of the disease. Low levels of CDC25B might contribute to the progression of the autoimmune arthritis and/or might be consequence of the inflammatory environment in the active disease. The possible role of DUSP7 and CDC25B as biomarkers of the disease in clinical protocols is discussed. mRNA profiling in peripheral blood CD4 T cells has identified the association of low transcript levels of DUSP7 and CDC25B with autoantibodies and the activity of early arthritis, respectively. Presented data suggest a potential role of transcript levels of these genes as biomarkers of the disease in clinical protocols.